Antioxidant capacity and enzymatical activity of basil ‘nufar’ (Ocimum basilicum L.) stored under cooling. - López-Blancas, Eduardo; Martínez-Damián, María Teresa; Colinas-León, María Teresa; Bautista-Boñuelos, Cecilio; Martínez-Solís, Juan; Rodríguez-Pérez, Juan Enrique (Agronomía Mesoamericana, 2014)
The present study aimed to evaluate the effect of refrigerated storage on the antioxidant activity (ability to capture free radicals) and enzymatic activity in basil ‘Nufar’. This study was conducted at Chapingo University (Texcoco, Mexico) during the spring-summer of 2012. Basil previously packed in plastic film was refrigerated at 5 and 10 °C, and at room temperature (20 °C - control) for 18 days. Every 48 hrs, total phenols, antioxidant capacity and the activity of the enzymes catalase, superoxide dismutase, peroxidase and polyphenol oxidase, were evaluated. Cooling at 5 °C had the highest catalase activity (14,3 U/mg/pro) and superoxide dismutase (2,9 U/mg/pro) at 2 and 4 days of storage, while peroxidase activity increased at 10 and 18 days of storage (57,6 and 74,9 U/mg/pro). At 10 °C the content of total phenols increased from 3,7 to 4,2 mg/kg/WF after 10 days of storage, and the antioxidant capacity from 47.5 to 79.1 mg VCEAC/g/WF after 8 days of storage; the activity of polyphenol oxidase also increased from 11,7 to 31,8 U/mg/pro after 10 days of storage. The storage at 5 °C affected the total phenolic content and antioxidant capacity as well as the enzymatic activity of peroxidase and polyphenol oxidase, and increased the activity of catalase and superoxide dismutase, and therefore, in order to reduce the activity of the oxidative enzmes, it is suggested to store basil “nufar” at 10 °C.